Genomic Susceptibility Loci for Brain Atrophy, Ventricular Volume, and Leukoaraiosis in Hypertensive Sibships - Turner, Stephen T. (2009)
OBJECTIVE: To localize susceptibility genes for alterations in brain structure associated with risk of stroke and dementia. We conducted genomewide linkage analyses for magnetic resonance imaging (MRI) measures of brain atrophy, ventricular, and subcortical white matter hyperintensity (leukoaraiosis) in 689 non-Hispanic white (673 sibling pairs; median age, 61 years) and 544 non-Hispanic black participants (503 sibling pairs; median age, 64 years) from sibships with at least 2 members with essential hypertension. DESIGN, SETTING, AND PATIENTS: We determined brain, ventricular, and leukoaraiosis volumes from axial fluid-attenuated inversion recovery MRI; we calculated brain atrophy as the difference between total intracranial and brain volumes. Microsatellite markers (n=451) distributed across the 22 autosomes were genotyped, and we used variance components methods to estimate heritability and assess evidence of genetic linkage for each MRI measure. MAIN OUTCOME MEASURES: Brain atrophy ventricular volume, and leukoaraiosis determined from fluid-attenuated inversion recovery MRI. RESULTS: In both races, the heritability of each MRI measure was statistically greater than 0 (P< .001), ranging in magnitude from 0.42 (for ventricular volume in blacks) to 0.69 (for brain atrophy in blacks). Based on multipoint logarithm of odds scores (MLS), the strongest evidence of genetic linkage was observed for brain atrophy on chromosomes 1 (MLS, 3.49 at 161 cM; P< .001) and 17 (MLS, 3.08 at 18 cM; P< .001) in whites; for ventricular volume on chromosome 12 (MLS, 3.67 at 49 cM; P< .001) in blacks and chromosome 10 (MLS, 2.47 at 110 cM; P < .001) in whites; and for leukoaraiosis on chromosome 11 (MLS, 2.21 at 118 cM; P < .001) in whites and chromosome 22 (MLS, 2.02 at 36 cM; P= .001) in blacks. CONCLUSIONS: The MRI measures of structural brain injury are heritable in non-Hispanic black and white sibships ascertained through hypertensive sibling pairs. The susceptibility loci for brain atrophy, ventricular volume, and leukoaraiosis identified by linkage analyses differ among MRI measures and between races.